Factors Involved in Maintaining Haemostasis in Patients with Myelodysplastic Syndrome - Fernández Bello, Ihosvany; Jiménez-Yuste, Víctor; de Paz, Raquel; Martín Salces, Mónica; Justo Sanz, Raul; Monzón Manzano, Elena; Arias-Salgado, Elena G.; Álvarez Román, María Teresa; Rivas Pollmar, María Isabel; Goyanes, Isabel; Butta, Nora V. (Thrombosis and Haemostasis, 2018)
Etiopathogenesis of myelodysplastic syndrome (MDS) might cause per se an anomalous haemostasis that can be even more deteriorated by thrombocytopaenia. So, evaluation of haemostasis in patients with MDS rises as a necessity.This work aimed to characterize haemostasis in non-bleeder MDS patients with a platelet count similar to healthy controls to establish differences between the two groups not related to thrombocytopaenia.Thromboelastometry in samples from MDS patients suggested the existence of at least two antagonistic processes: one of them giving a hypocoagulable pattern (prolonged clotting time and lower α angle) and another conferring a procoagulant profile (decreased fibrinolysis). Hypocoagulable state might be due to a decreased ability of platelets to be stimulated and to the presence in plasma of a factor/s that prolonged the time to initiate thrombin generation. This factor/s might be antibodies as this effect was observed in samples from MDS patients with an associated autoimmune-inflammatory condition.Otherwise, hypercoagulable state seemed to rely on an increased presence of red cell- and monocyte-derived microparticles and to the increased exposure of phosphatidylserine that served as scaffold for binding of coagulation factors.We concluded that haemostasis in MDS patients is a complex process influenced by more factors than platelet count.
Keywords: platelets; microparticles; thromboelastometry; MDS; prothrombinase complex